Efficacy and Safety of Secukinumab in Patients with Plaque Psoriasis and Latent Tuberculosis - Ribero, Simone (Case Rep Dermatol, 2019)
Upon the association of biologic treatments with reactivation of latent tuberculosis infection (LTBI), screening for Mycobacterium tuberculosisinfection and anti-tuberculosis chemoprophylaxis in positive patients are required prior to biologic drug administration. Nevertheless, the risk of infection relapses associated with biologic drugs seems to be different. No cases of reactivation of LTBI have been observed in secukinumab-treated subjects, in contrast with clinical reports on the risk associated with anti-tumor necrosis factor Α-based therapy. Twelve patients with moderate to severe plaque psoriasis eligible for systemic treatment and found to have LTBI received secukinumab without previous chemoprophylaxis initiation because of clinical contraindication for 10 cases and refusal by 2 patients. None of them had tuberculosis reactivation.